TWITTER: Expressing Hate Speech Behind Tweeting - Yudha Wirawanda; Tangguh Okta Wibowo (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
This study explores on how Indonesian people use Twitter. Only one hundred and forty (in one tweet) characters are able to create unlimited tweets expressing an agenda, Twitter has a role as canalization of desire that their users cannot devote in offline world. This study will focus on the prosumption practice toward the use of Twitter behind tweeting to spread a variety of opinions, including hate speech, because the characters of cyberspace allow the formation of habitus toward virtual users that they can devote freely a certain emotion in cyberspace. This study critically analyzes the prosumption practices of creating hate speech behind tweeting. This study also discusses on how Twitter's characters are able to express hate speech by the users. The interaction of users to use Twitter in expressing hate speech has played a role on how the users construct the world.